Automatic C library wrapping Ctypes from the trenches - Kloss, Guy K. (Massey University, 2009)
At some point of time many Python developers at least in computational science will face the situation that they want to interface some natively compiled library from Python. For binding native code to Python by now a larger variety of tools and technologies are available. This paper focuses on wrapping shared C libraries, using Python's default Ctypes. Particularly tools to ease the process (by using code generation) and some best practises will be stressed. The paper will try to tell a step by step story of the wrapping and development process, that should be transferable to similar problems.
Keywords: Python (Programming language); Code generation; C libraries; Ctypes